Standing Still at Full Speed: Sports in an Overheated World - Eriksen, Thomas Hylland (Frontiers in Sports and Active Living, 2021)
In evolutionary biology, the “Red Queen Effect” refers to a form of inter- or intra-species competition where continuous improvement is necessary in order to survive and thrive, since the other species/individuals evolve. In sport, the same mechanism can be easily observed, and this article explores its implications. It discusses improved training regimes, scientific diets, innovative techniques enhancing performance, and technological improvements such as fibreglass skis. It argues that the upward spiral of improved achievement can be seen as an effect of the global market, or of the modern values of development and growth which are celebrated in modern sports. The world of competitive sports is not just an integral part of global capitalism, but it also mirrors and mimes its internal logic. The kinship between sport and war is obvious, and many sports grew out of military training. But since much of the world has been spared the horrors of war for generations, in the very same period that capitalism has become ever more hegemonic and globalised, sports in the 21st century have come to resemble market competition more than bloody events on the battlefield. Not least for this reason, the treadmill paradox, or Red Queen effect, easily discernable in market economies as a driver for change, whether progressive or destructive or both, can fruitfully be applied as an analytical lens through which to view sport. The question nevertheless remains to be answered as to whether the improved achievements of athletes lead to an improved spectator experience or the opposite. In this question lies an inherent paradox of contemporary world civilisation, with a literal as well as a metaphorical bearing on the critique of the unsustainable growth economy.